Case Report: IL-21 and Bcl-6 Regulate the Proliferation and Secretion of Tfh and Tfr Cells in the Intestinal Germinal Center of Patients With Inflammatory Bowel Disease - Yang, Youguang; Lv, Xiaodan; Zhan, Lingling; Chen, Lan; Jin, Hui; Tang, Xinping; Shi, Qingqing; Zou, Qiyuan; Xiang, Jiqiao; Zhang, WeiWei; Zeng, Zhaojing; Jiang, Haixing; et al. (Frontiers in Pharmacology, 2021)
Objective: This study aimed to investigate the effect of interleukin (IL)-21 and B cell lymphoma protein-6 on germinal center follicular helper T (Tfh) cells and follicular regulatory T (Tfr) cells and its relationship with the clinical features of inflammatory bowel disease (IBD). Methods: The expression of peripheral blood cytokines IL-21 and Bcl-6 mRNA was detected by reverse transcription–polymerase chain reaction. The distribution characteristics of Tfh and Tfr cells were detected using the triple immunofluorescence staining analysis. Results: The expression of IL-21 and Bcl-6 mRNA was upregulated in the ulcerative colitis (UC) and Crohn disease (CD) groups compared with that in the control group. Triple immunofluorescence staining showed that the number of Tfh cells in the intestinal germinal center obviously increased in the UC and CD groups compared with that in the control group, whereas the number of Tfr cells reduced. Conclusion: This study suggested that the Tfr and Tfh cells might be involved in the regulation of IBD. Bcl-6 and IL-21 can regulate the Tfh/Tfr ratio in the intestinal germinal center, promoting the occurrence and development of IBD.